Implementasi Media Sosial Sebagai Media Pembelajaran Untuk Meningkatkan Keterampilan Berbicara Teks Tanggapan Mengenai Buku Fiksi di SMP Negeri 4 Madiun - Elysa Nurfarahana; Eni Winarsih; Sri Andayani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
An incident that often happens nowadays is that students prefer to play on their cellphones to watch videos. Especially in applications like TikTok which are not specifically for education. Many of the videos on the app are not filtered, so there is a possibility that underage students are watching inappropriate content. Therefore, an understanding of this application is necessary in order to achieve learning objectives. This article aims to provide knowledge about the use of TikTok and YouTube to improve students' speaking skills through the use of these applications. This type of research is Classroom Action Research (PTK) which covers pre-cycle, cycle I and cycle II. There are four research procedures, namely planning, implementation, observation and finally reflection. This research was carried out at SMP Negeri 4 Madiun with research subjects in class VII B which had a total of 32 students. The data analysis technique used is qualitative data. The results of this research contain: 1) the learning outcomes in the Pre-cycle were that class VII B students had a knowledge score of 25% while the attitude score was 12.5%; 2) the learning results in Cycle I of students experienced an increase in the percentage of complete knowledge values ​​by 46% while the attitude values ​​were 50%; 3) learning outcomes in Cycle II experienced a better improvement than the previous stage with a completeness percentage of knowledge scores of 100% and attitude scores reaching 97%.